Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Simplify (3 - √7)(5 + √7)

Sagot :

You can use F.O.I.L. for this, which if you don't know stands for first outer inner last, so multiply the first in each parentheses, then the outer, then the inner, then the last. yours would be 3*5+3*√7+(-√7)*5+(-√7)*√7 => 15+3√7-5√7-7 => 8-2√7
Final answer:
8-2√7
Hope I could help :)
(3-√7)(5+√7)
FOIL
F-Multiply the First to numbers 3×5=15
O-Multiply the Outter two numbers 3×√7=3√7
I-Multiply the Inner two numbers -√7×5=-5√7
L-Multiply the last two numbers -√7×√7=-7
Put it together and you get
15+3√7-5√7-7
Combine the like terms 15-7=8 and 3√7 - 5√7=-2√7
And you get 8-2√7